Improved Human Muscle Biopsy Method To Study Neuromuscular Junction Structure and Functions with Aging. (15th December 2019) - Aubertin-Leheudre, Mylene; Pion, Charlotte H; Vallée, Joanne; Marchand, Sandrine; Morais, José A; Bélanger, Marc; Robitaille, Richard
Abstract: Reduced mobility and physical independence of elders has emerged as a major clinical and public health priority with extended life expectancy. The impact of the neuromuscular function on muscle activity and properties has emerged as a critical factor influencing the progress and outcome of muscle changes with aging. However, very little is known about the neuromuscular junctions (NMJs) in humans, in part due to technical constraints limiting the access to healthy, fresh neuromuscular tissue. Here, we describe a method, called B iopsy using E lectrostimulation for E nhanced NMJ S ampling (BeeNMJs) that improves the outcome of muscle biopsies. We used local cutaneous stimulation to identify the area enriched with NMJs for each participant at the right Vastus lateralis (VL). The needle biopsy was then performed in proximity of that point. The BeeNMJs procedure was safe for the participants. We observed NMJs in 53.3% of biopsies in comparison with only 16.7% using the traditional method. Furthermore, we observed an average of 30.13 NMJs per sample compared to only 2.33 for the traditional method. Importantly, high-quality neuromuscular material was obtained whereby pre-, postsynaptic, and glial elements were routinely labeled, simultaneously with myosin heavy chain type I. The BeeNMJs approach will facilitate studies of NMJs, particularly in human disease or aging process.